IMPLEMENTASI TEMBANG DOLANAN SEBAGAI MEDIA STIMULASI KEMAMPUAN BERBAHASA JAWA ANAK USIA 4–5 TAHUN - Rahmawati, Ika Dewi; Firdausi Nuzula Apriliyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of tembang dolanan as a medium for stimulating Javanese language skills in children aged 4–5 years, describe the development of children's Javanese language skills during the implementation of tembang dolanan, and identify supporting and inhibiting factors in its implementation. The study uses a qualitative approach with a case study research type conducted at PGRI Bina Siswa Kindergarten Gedongombo Tuban. The research subjects consisted of teachers, principals, parents, and 20 children in group A. Data collection techniques included observation, interviews, and documentation. Data analysis employed the Miles, Huberman, and Saldaña model, which includes data reduction, data presentation, and conclusion drawing. The results showed that the implementation of tembang dolanan (traditional Javanese songs) was carried out through singing activities combined with games, movement, and the familiarization of using simple Javanese. The development of children's Javanese language skills is evident in their increasing vocabulary mastery, listening skills, imitation skills, and their confidence in using simple Javanese in everyday communication. Supporting factors include the active role of teachers, school support, the use of games, and children's enthusiasm. Inhibiting factors include the dominance of Indonesian in the family environment, differences in children's language abilities, limited learning media, and limited time for activities.